REGULATION OF THE RATE OF GEL FORMATION BY ADDING CHEMICAL COMPOUNDS INTO SILICATECOMPOSITIONS - Titova, Оlga; Hrushak , Zoia; Kravchuk , Tetiana; Yefymenko, Valerii; Maksumiuk, Mariia (Proceedings of National Aviation University (archive), 2021)
Purpose: The purpose of this article is to determine the dependence of the rate of gel formation on the type of reagent-inhibitor of the gel formation process, and to study the kinetic dependences of gel formation of silicate compositions in the presence of compounds that regulate the rate of gel formation. Research methods: Direct and reverse titration, potentiometric titration, pH-metry, determination of the dynamic viscosity on a rotational viscometer, axial compression method to determine the elastic modulus were used to study the possibility of using chemical reagents as gelation inhibitors. Results: The possibility of using inorganic and organic additives to slow down the gel formation process and the effect of these additives on the strength of the gel, their thermodynamic parameters have been researched. Discussion: The adding of organic acids into the silicate composition as "crosslinking agents" slows down the gel formation process, while replacing hydrochloric acid with other gel acids that slow down the gel formation process does not lead to a decrease in the strength characteristics of these systems compared to the standard. It was found that with an increase in the gelation time, the strength of the gels decreases, and the syneresis increases; the adding of inhibitor additives insignificantly worsens the filterability of silicate compositions, which in general have bad filterability, leading to an increase in resistance during filtration at the inlet section of the sample. Observations have shown that the addition of additives-inhibitors does not affect the thermal stability of gels, regardless of the additives' nature.